Oralität und Literalität: Wie polnische Deutschlerner den Unterschied zwischen gesprochener und geschriebener Sprache auf Textebene wahrnehmen - Machowicz, Iwona (Wydawnictwo Naukowe UAM, 2013)
The present paper deals with both medium and conception of orality and literality on text level, and aims at giving an outline of some important aspects underlying the discussion about the differences between written and spoken language and their impact on Polish learners of German.
Orality and literality: How Polish learners of German perceive the distinction between spoken and written language on text level
Keywords: spoken language (orality); written language (literality); medium; conception; foreign language writing